Relationship between sediments and water turbidity in coral reefs around Ishigaki Island, the Ryukyus - Nagao, M.; Inoue, M.; Fujioka, Y.; Suzuki, A.; Morimoto, N.; Iwase, A.; Shibuno, T.; Tottori, K.; Ohba, H.; Kan, H. (Journal of the Japanese Coral Reef Society, 2004)
The distributions of sediments and its relation to reef water turbidities were investigated in three fringing reefs along the east coast of Ishigaki Island and a patch reef named “Shimobishi” in the lagoon of Sekisei Reef. In order to quantify fine particles in sediments, we employed “SPSS (content of suspended particles in sea sediments)” method, which was originally proposed by Ohmija (1987) for quick assessment of land-derived soil distribution in reef sediments. We found highest SPSS values in a moat and channel bottom of the Miyara Bay and along the northern coast of the Todoroki River mouth in Ishigaki Island. In contrast, SPSS values were low in other three reefs including Yasurazaki, Shiraho and Shimobishi areas. Reef water turbidities showed significant correlation with SPSS values, which suggests that the major cause of reef water turbidities is resuspension of fine particles in the sediments. Accuracy and precision of the measurements can be increased by using a portable turbidimeter in the original SPSS method. The modified method has the potential for applying to a study of under-water light environment, which may influence coral-algal competitions in degrading reef conditions.